Analysis of Sexual Orientation among Adolescents in Tasikmalaya Regency - Azzahroh, Putri; Silawati, Vivi; Zhau, Weihuan Zhau; Sopiatunnida , Ulfah Aunillah (International Health Sciences Journal, 2023)
Background: The age range of these high school students is 13-16 years, which is the initial age of showing homosexual behavior and same-sex attraction. To prevent deviant sexual behavior from occurring in adolescents, it is necessary to identify sexual orientation in the early stages. Objective: To determine the sexual orientation of adolescents at SMPN 1 Sariwangi and SMP Islam Jayaratu. Determining the influence of personality, environment, trauma, sexual behavior, intensity of access to pornography, social support, parenting style, religiosity, attitudes, and perceptions of LGBT towards sexual orientation. Determining the differences of adolescent sexual orientation at SMPN 1 Sariwangi and SMP Islam Jayaratu. Methodology: This research is a descriptive research with a cross-sectional approach with the PLS-SEM test and the difference test. The sample in this research was 227 teenagers. The research instrument used a questionnaire. Results: Based on the research conducted, it was found that the sexual orientation of 95% of adolescents was heterosexual and the remaining 5% had a deviant sexual orientation, homosexual or bisexual. Factors significantly influenced the sexual orientation are the intensity of access to pornography, environment and trauma. Conclusion: Most of the adolescents at SMPN 1 Sariwangi and SMP Islam Jayaratu are heterosexual. Access intensity of pornography, environment and trauma had a significant effect on the formation of sexual orientation.